Metabolic Properties of Lowdensity Lipoprotein (LDL) Triglycerides in Patients with Type 2 Diabetes, Comparison with Small Dense LDL-Cholesterol - Suzuki, Natsuko; Kodera, Rieko; Hirashima, Takeshi; Aoki, Ema; Koba, Shinji; Satoh, Noriyuki; Ito, Yasuki; Hirano, Tsutomu; Oshima, Taito; Hosoya, Mitsuru; Hayashi, Toshiyuki; Ohta, Motoko (Journal of Atherosclerosis and Thrombosis, 2022)
Aims: Abnormal compositional changes in low-density lipoprotein (LDL) particles, such as triglyceride (TG) enrichment and size reduction, are common in patients with diabetes. Several cohort studies have demonstrated that LDL-TG and sdLDL-cholesterol (C) are sensitive biomarkers for predicting atherosclerotic cardiovascular diseases beyond LDL-C. Although sdLDL has been extensively studied, little is known about the properties of LDL-TG. We investigated similarities or differences between LDL-TG and sdLDL-C.Methods: Fasting plasma was obtained from 1,085 patients with type 2 diabetes who were enrolled in the diabetes regional cohort study (ViNA Cohort). LDL-TG and sdLDL-C concentrations were measured using a homogeneous assay established by us. In a subset of subjects, LDL-TG and sdLDL-C levels were measured postprandially or after treatment with lipid-lowering drugs.Results: In a quartile analysis, higher LDL-TG quartiles were associated with higher frequency of female and fibrate users, whereas sdLDL-C quartiles were associated with frequency of men, drinking, and metabolic syndrome-related measurements. Higher quartiles of LDL-TG/LDL-C were associated with smoking, drinking, fibrate users, and statin users. LDL-TG was significantly correlated with TG, LDL-C, sdLDL-C, and apolipoprotein (apo) B, with apoB being the primary determinant. LDL-TG correlated to high sensitive C-reactive protein (CRP) independently of other lipids. Mean LDL-TG did not change with fasting/non-fasting. Statin treatment reduced LDL-TG, whereas fibrates increased it, but these drugs reduced sdLDL-C equally.Conclusions: LDL-TG levels were more tightly regulated by the number of LDL particles than plasma TG levels were. SdLDL-C was closely associated with metabolic syndrome-related factors, whereas LDL-TG was associated with low-grade systemic inflammation.